Volutidae (Mollusca: Gastropoda) of the Lakhra Formation (Earliest Eocene, Sindh, Pakistan): systematics, biostratigraphy and paleobiogeography - Merle, Didier; Pacaud, Jean-Michel; Métais, Grégoire; Bartolini, Annachiara; Lashari, Rafiq A.; Brohi, Imdad A.; Solangi, Sarfraz H.; Marivaux, Laurent; Welcomme, Jean-Loup (Zootaxa, 2014)
The paleobiodiversity of the Volutidae (Mollusca: Gastropoda) of the Ranikot Group (Sindh, Pakistan) and particularly of the Lakhra Formation (SBZ 5 biozone, Earliest Eocene), is reconsidered on the basis of new material collected during recent field trips. Ten new species are described (Mitreola brohii sp. nov., Lyrischapa vredenburgi sp. nov., L. brevispira sp. nov., Athleta (Volutopupa) citharopsis sp. nov., A. (Volutocorbis) lasharii sp. nov., Volutilithes welcommei sp. nov., V. sindhiensis sp. nov., Pseudaulicina coxi sp. nov., Sindhiluta lakhraensis sp. nov. and Pakiluta solangii sp. nov.) and one species is in open nomenclature (Lyria sp.). Three new genera are described: Lyriopsis gen. nov. [Volutinae, ?Lyriini, type species: Lyriopsis cossmanni (Vredenburg, 1923)], Sindhiluta gen. nov. [Volutilithinae, type species: Sindhiluta lakhraensis n. sp.] and Pakiluta gen. nov. [?Volutodermatinae, type species: Pakiluta solangii n. sp.]. Two new combinations are proposed: Lyriopsis cossmanni (Vredenburg, 1923) comb. nov. and Athleta (Volutopupa) intercrenatus (Cossmann & Pissarro, 1909) comb. nov. Lectotypes are designated for Lyria cossmanni Vredenburg, 1923, L. feddeni Vredenburg, 1923, Volutospina noetlingi Cossmann & Pissarro, 1909, V. intercrenata Cossmann & Pissarro, 1909 and Athleta (Volutocorbis) victoriae Vredenburg, 1923. With 21 species, this volutid fauna is the most diverse recorded from the Tethys Ocean during Earliest Eocene time. The assemblage is characterized by a strong turnover marked by regional speciation and the appearance of many western Tethyan invaders. Although at the species level, the assemblage documents a strong provincialism, at the genus level, the high number of shared genera between Eastern Tethyan and Old World Tethyan realms begins a phase of long-term homogeneity of volutid assemblages from the Tethyan paleobiogeographic province.